First report of the fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae), natural enemies from Africa. (13th June 2018) - Sisay, Birhanu; Simiyu, Josephine; Malusi, Peter; Likhayo, Paddy; Mendesil, Esayas; Elibariki, Nsami; Wakgari, Mulatu; Ayalew, Gashawbeza; Tefera, Tadele
Abstract: The fall armyworm (FAW), Spodoptera frugiperda, is a major pest of maize in North and South America. It was first reported from Africa in 2016 and currently established as a major invasive pest of maize. A survey was conducted to explore for natural enemies of the fall armyworm in Ethiopia, Kenya and Tanzania in 2017. Smallholder maize farms were randomly selected and surveyed in the three countries. Five different species of parasitoids were recovered from fall armyworm eggs and larvae, including four within the Hymenoptera and one Dipteran. These species are new associations with FAW and were never reported before from Africa, North and South America. In Ethiopia, Cotesia icipe was the dominant larval parasitoid with parasitism ranging from 33.8% to 45.3%, while in Kenya, the tachinid fly, Palexorista zonata, was the primary parasitoid with 12.5% parasitism. Charops ater and Coccygidium luteum were the most common parasitoids in Kenya and Tanzania with parasitism ranging from 6 to 12%, and 4 to 8.3%, respectively. Although fall armyworm has rapidly spread throughout these three countries, we were encouraged to see a reasonable level of biological control in place. This study is of paramount importance in designing a biological control program for fall armyworm, either through conservation of native natural enemies or augmentative release.